Locust bean gum hydrolysis : impact on molecular and functional properties : a thesis presented in partial fulfilment of the requirements for the degree of Master in Food Technology, at Massey University, Manawatu, New Zealand - Gao, Ge (Massey University, 2021)
Locust bean gum (LBG) is a widely encountered additive in the food industry, with particular application in ice cream production, functioning as a viscosifier and stabilizer, where it reduces ice crystallization and slows down the melting rate. However, its incompatibility property with milk proteins, especially when mixed under high concentrations can lead to phase separation and wheying, often necessitating the use of additional stabilisers such as carrageenan, to mitigate this issue. Enzymatic hydrolysis was hypothesised as a potential method to modify the LBG structure, and thus its phase behaviour, by breaking native LBG chain into fractions with lower molecular weight. It was also anticipated that this would also reduce the LBG viscosity in solution. In this study, the rheological behaviour of LBG during enzymatic hydrolysis was explored and the impact of hydrolysis on phase behaviour in model LBG/skim milk powder (SMP) solutions containing milk protein was studied. The effect of hydrolysis of LBG on its functional properties in ice cream was also investigated. β-mannanase was chosen to hydrolyse the LBG. Rheological results indicated that the enzymatic hydrolysis could be used to progressively reduce relative viscosity of solution, noting that termination of the reaction was made challenging by the high heat stability observed for the enzyme. The results of Confocal Laser Scanning Microscope (CLSM) as well as the phase diagram plotted for LBG/SMP mixtures implied that hydrolysis of LBG slowed down the phase separation process. This was also evident when being applied in the ice cream making. Hydrolysis of LBG showed a more compatible result with protein during the aging stage. Interestingly, hydrolysis of LBG did not have significant effect on other properties in the ice cream, with a relatively low overrun value (73.3%) compared to the non-hydrolysed LBG (94.4%), and a slightly higher meltdown rate (0.26g/min) compared to the normal LBG (0.24g/min). Overall, hydrolysis of LBG can improve the compatibility of polysaccharide/protein mixtures and has a promising prospect to be applied in the food industry.
Figure 2.3 (=Dhawan & Kaur, 2007 Fig 2) was removed for copyright reasons.
Keywords: 300607 Food technology